“Robust Notice” and “Informed Consent:” The Keys to Successful Spyware Legislation - Blanke, Jordan M. (Science and Technology Law Review, 2006)
As spyware, adware, and other computer programs that surreptitiously monitor user behavior become more prevalent, the United States Congress and a number of state governments have proposed legislation to target this problem. This article argues that any legislative solution must require robust, meaningful notice to users about the ramifications of the software they are installing, so that users can give their informed consent to install the software and accept its terms and conditions. The article discusses the background of the technological innovations that led to the present day computing environment. It then explores some of the common questions and answers that arise concerning spyware and discusses the strengths and weakness of various state and federal legislative approaches.